The Influence of PBL Model Based on Ethnomathematics on Critical Thinking Skills Reviewed from the Character of Love for the Country in Junior High Schools - David, Guido; Yusnidar, Yusnidar; Laukanova, Roussanka; Kertesz, David Csaba; Koirala, Raj Kumar (Interval: Indonesian Journal of Mathematical Education, 2024)
Purpose of the study: This study aims to analyze the effect of the Problem-Based Learning (PBL) model integrated with ethnomathematics on students' critical thinking skills, considering the mediating role of curiosity. Methodology: This study uses a quantitative approach using Structural Equation Modeling-Partial Least Squares (SEM-PLS) to evaluate the relationship between variables. Indicators for the PBL model include understanding of ethnomathematics concepts, cultural relevance, student engagement, and effectiveness in learning. Critical thinking skills are assessed through basic clarification, inference, and strategy, while curiosity is measured by attention, questioning, and comparison. Main Findings: The results showed that the ethnomathematics-based PBL model significantly improved students' critical thinking skills, with a direct effect of 0.68 and a total effect of 0.92 when mediated by curiosity (indirect effect 0.24). This model explains 62% of the variance in critical thinking skills and 29% in curiosity. This study introduces a novel integration of cultural context into a PBL framework, showing that embedding local traditions enhances cognitive engagement and critical thinking in a meaningful way. Novelty/Originality of this study: The findings suggest that incorporating ethnomathematics into PBL not only enhances cognitive skills but also fosters curiosity, offering an effective and culturally responsive teaching strategy.